(untitled) (Global Journal of Medical Research, 2022)
People with opioid use disorder (OUD) have rates of cigarette smoking approaching 90% and smoking cessation programs are rarely effective. The relationship between long-term opioid exposure and smoking has been epidemiologically observed but not well understood. Nicotine interacts with the nicotinic acetylcholine receptors in the central and peripheral nervous systems, which are involved in anxiety, cognition, sleep, arousal, and pain perception. Cigarette smoking triggers the release of dopamine in the brain. There is equivocal evidence that nicotine may have an analgesic effect, but paradoxically, smokers tend to have higher pain intensity levels than nonsmokers. Pharmacologic treatments for nicotine dependence were often studied in trials that routinely excluded subjects with opioid dependence. Further, the association between smoking and long-term opioid use sometimes includes mental health disorders and/or chronic pain. In fact, smoking may also be comorbid with chronic pain. It has been speculated that smoking, particularly at a young age, may be predictive of OUD. While smoking is also associated with other forms of substance abuse, the association between OUD and tobacco is particularly intriguing and likely involves common neurobiological pathways.